2016
DOI: 10.1002/adom.201500549
|View full text |Cite
|
Sign up to set email alerts
|

Optical Acetone Vapor Sensors Based on Chiral Nematic Liquid Crystals and Reactive Chiral Dopants

Abstract: Accurate monitoring of exposure to organic vapors, such as acetone, is an important part of maintaining a safe working environment and adhering to long-and short-term exposure limits.Here, a novel acetone vapor detection system is described based on the use of a reactive chiral dopant in a nematic liquid crystal thin film, which can accurately monitor the total exposure over a given timeframe through changes in the reflection band of the film. It was found that films exposed to 1000 parts per million by volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 33 publications
(29 reference statements)
0
19
0
3
Order By: Relevance
“…Another approach to using chiral dopants is based on the principle that, upon reaction with a specific analyte, the dopant will respond with either a chemical or a supramolecular way, leading to changes in the reflected color. [ 99,160 ] For example, Cachelin et al [ 161 ] have recently developed a time‐integrating sensor, which can serve as a chemical dosimeter by measuring the total exposure to an analyte over a given time frame. In their work, they described an acetone vapor detection system, based on a film of E7 doped with tetraaryl‐1,3‐dioxolane (TADDOL)–phenylhydrazine complex.…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 99%
“…Another approach to using chiral dopants is based on the principle that, upon reaction with a specific analyte, the dopant will respond with either a chemical or a supramolecular way, leading to changes in the reflected color. [ 99,160 ] For example, Cachelin et al [ 161 ] have recently developed a time‐integrating sensor, which can serve as a chemical dosimeter by measuring the total exposure to an analyte over a given time frame. In their work, they described an acetone vapor detection system, based on a film of E7 doped with tetraaryl‐1,3‐dioxolane (TADDOL)–phenylhydrazine complex.…”
Section: Functional Liquid Crystal Materialsmentioning
confidence: 99%
“…Liquid crystals (LCs), which combine key properties of crystalline solids (long‐range order) and isotropic liquids (molecular mobility), are a promising class of chemoresponsive materials because the orientations of molecules (mesogens) within LCs, termed the director, can be changed by subtle interactions between mesogens and chemical functional groups presented at surfaces . For example, past studies have shown that mesogens with specific functional groups (for example, nitrile or pyrimidine) can bind to metal cations presented at surfaces, and that competitive binding of chemical species such as organophosphonates can disrupt those binding interactions to trigger ordering transitions in the LC . The ordering transitions are visible to the naked eye or can be quantified using simple optical methods.…”
Section: Methodsmentioning
confidence: 99%
“…На их основе разрабатываются гибкие магниты [13], светочувствительные наноструктуры [14], хирооптические молекулярные переключатели [15][16][17] и микролинзы для биомиметических оптических систем [18]. В работах [19,20] показана возможность создания высокочувствительных и селективных сенсоров для обнаружения газов на основе ЖК и химически активных хиральных допантов. Существенный практический интерес может вызвать использование фоточувствительных ЖК допантов в органических солнечных ячейках [21].…”
Section: индуцированные спиральные жидкокристаллические фазыunclassified